05 Co-design of a logic model describing components, mechanisms of change and expected impacts of case management for people who frequently call ambulance services. Issue 9 (19th August 2021) - Aslam, Rabeea'h; Cole, Robert; Diethart, Berni; Edwards, Adrian; Edwards, Bethan M; Evans, Bridie A; Foster, Theresa; Fothergill, Rachael; Gripper, Penny; Hughes, Heather; John, Ann; Khanom, Ashra; et al.
Abstract : Background: Multi-agency case management is being introduced by ambulance services and their partners in the UK to try to identify and address the needs of those who call 999 ambulance services frequently. However, there is a lack of evidence about what works well in this setting and how. Based on current nationally agreed definitions, calling frequently is defined as 5 or more times in a month, or 12 or more times in a three-month period. The STRETCHED study (STR ategies to manage E mergency ambulance T elephone C allers with sustained H igh needs – an E valuation using linked D ata) study seeks to evaluate clinical and cost-effectiveness, safety, and efficiency of case management for people who frequently call the emergency ambulance service. We developed a logic model to describe key components, mechanisms of change and expected impacts of cross-sectoral case management approaches to the management of people who call 999 frequently. Method: We conducted a stakeholder event with 37 people from Wales, England and Northern Ireland including patient representatives and professional staff involved in commissioning, planning and delivering case management for people who call 999 services frequently. The aggregated responses from the participants was used as the basis for developing a logic model. Results: Components: dedicated staff time for case management, availability and knowledge of relevant services for referral, multidisciplinary collaboration, organisational support, and clear information sharing protocols Mechanisms: provision of space for a clear understanding of reasons for calling, tailoring of multi–sectoral management to individual needs, offering therapeutic support and assistance in development of self–efficacy Impacts: improvement in access to appropriate and timely care, increase in efficiency and accessibility of the healthcare system, reduction in emergency calls, costs and mortality Conclusion: Case management is a developing area of provision in prehospital emergency care for people who call ambulance services frequently. Our logic model provides a firm foundation for evaluation to build the urgently needed evidence base for case management of people who call ambulance services frequently.